A revised method for reconstructing the hydrocarbon generation and expulsion history and evaluating the hydrocarbon resource potential: Example from the first member of the Qingshankou Formation in the Northern Songliao Basin, Northeast China. (November 2020) - Li, Changrong; Pang, Xiongqi; Huo, Zhipeng; Wang, Enze; Xue, Nan
Abstract: Reconstructing the hydrocarbon generation and expulsion history of source rocks is an essential part of evaluating the hydrocarbon resource potential by genetic method. The hydrocarbon generation potential method is an efficient tool for quantifying the hydrocarbon generation and expulsion characteristics of source rock and evaluating the hydrocarbon resource potential based on Rock-Eval data. Although various revised versions of the method are publicly available, the following problems remain to be resolved: (a) the method is subjective; (b) implicit limitations are observed; and (c) rock mass loss is not considered, which may result in unacceptable errors. In this study, we propose a revised hydrocarbon generation potential method. Expressions for calculating the original rock mass (Go ), original total organic carbon (TOCo ), transformation ratio (TR ), hydrocarbon expulsion ratio (ER ) and hydrocarbon expulsion efficiency (f) were developed and incorporated into the hydrocarbon generation and expulsion history reconstruction and hydrocarbon resource potential evaluation, and these expressions combined conventional and unconventional resource evaluations systematically with objective and accurate results. The first member of the Qingshankou Formation (K2 qn1 ) in the Northern Songliao Basin, Northeast China, was used as an example to demonstrate the application of the proposed method. The results have been compared with the unrevised method using the same Rock-Eval data sets and verified with previous reports to demonstrate its reliability. The results also indicate that the hydrocarbon generation threshold (HGT) and hydrocarbon expulsion threshold (HET) of K2 qn1 are Ro = 0.4% and Ro = 0.6%, respectively. Three hydrocarbon generation and expulsion peak stages were identified: K2 n (81–74 Ma), K2 m (74–66 Ma), and N2 t (66–0 Ma). The hydrocarbon generation and expulsion centers of K2 qn1 are mainly the Qijia-Gulong Sag and Sanzhao Sag. The resource potentials of conventional oil, unconventional tight oil, and shale oil associated with K2 qn1 source rocks in the Northern Songliao Basin are 8.15 × 10 8  t, 22.97 × 10 8  t, and 62.1 × 10 8  t, respectively.